Industrial Enzymes Structure, Function and Applications - Polaina, Julio; MacCabe, Andrew P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Man's use of enzymes dates back to the earliest times of civilization. Important human activities such as the production of certain types of foods and beverages, and the tanning of hides and skins to produce leather for garments, serendipitously took advantage of enzyme activities. Important advances in our understanding of the nature of enzymes and their action were made in the late 19th and early 20th centuries, seeding the explosive expansion from the 1950s and 60s onward to the present billion dollar enzyme industry. Recent developments in the fields of genetic engineering and protein chemistry are bringing ever more powerful means of analysis to bear on the study of enzyme structure and function that will undoubtedly lead to the rational modification of enzymes to match specific requirements as well as the design of new enzymes with novel properties. This volume reviews the most important types of industrial enzymes, covering in a balanced manner three interrelated aspects of paramount importance for enzyme performance: three-dimensional protein structure, physicochemical and catalytic properties, and the range of both classical and novel applications. The material covered will be of interest to undergraduate and graduate students in biochemistry, biotechnology and applied microbiology in addition to researchers and industrialists.
Carbohydrate Active Enzymes -- Amylolytic Enzymes: Types, Structures and Specificities -- The Use of Starch Processing Enzymes in the Food Industry -- Cellulases For Biomass Conversion -- Cellulases in the Textile Industry -- Xylanases: Molecular Properties and Applications -- Microbial Xylanolytic Carbohydrate Esterases -- Structural and Biochemical Properties of Pectinases -- ?-L-rhamnosidases: Old and New Insights -- Application of Glycosidases and Transglycosidases in the Synthesis of Oligosaccharides -- Peptidases -- An Introduction to Peptidases and the Merops Database -- Cysteine Proteases -- Subtilisin -- Aspartic Proteases Used in Cheese Making -- Metalloproteases -- Aminopeptidases -- Lipases -- Lipases: Molecular Structure and Function -- Use of Lipases in the Industrial Production of Esters -- Use of Lipases in Organic Synthesis -- Use of Lipases for the Production of Biodiesel -- Use of Lipases in the Synthesis of Structured Lipids in Supercritical Carbon Dioxide -- Nucleic Acids Enzymes -- Restriction and Homing Endonucleases -- DNA Polymerases for PCR Applications -- Prokaryotic Reverse Transcriptases -- Dicer: Structure, Function And Role In RNA-Dependent Gene-Silencing Pathways -- Oxidoreductases and Other Enzymes of Diverse Function -- Hydrogen Peroxide Producing and Decomposing Enzymes: their Use in Biosensors and other Applications -- Laccases: Biological Functions, Molecular Structure and Industrial Applications -- High Redox Potential Peroxidases -- Amino Acid Dehydrogenases -- Phytase: Source, Structure and Application -- Nitrile Hydrolases -- Aspartases: Molecular Structure, Biochemical Function and Biotechnological Applications -- Transglutaminases -- Penicillin Acylases -- Hydantoinases.
Keywords: CHEMISTRY; BIOTECHNOLOGY; MICROBIOLOGY; BIOCHEMICAL ENGINEERING; FOOD SCIENCE; CHEMICAL ENGINEERING; CHEMISTRY; BIOTECHNOLOGY; APPLIED MICROBIOLOGY; BIOCHEMICAL ENGINEERING; FOOD SCIENCE; INDUSTRIAL CHEMISTRY/CHEMICAL ENGINEERING